Human Rights Education at University Level: UN Position and Vietnamese Perspective - Giao, Vu Cong; Duong, Nguyen Thuy (VNU Journal of Science: Legal Studies, 2022)
The article analyzes the concept, content, and importance of human rights education; the position of the United Nations in this regard; the current status of human rights education in Vietnam, with a focus on human rights education at the tertiary education level. The authors demonstrate that the promotion of human rights education in general, especially at the university level, is an urgent requirement in Vietnam today to implement the relevant resolutions of the United Nations General Assembly. According to the authors, to promote human rights education at the higher education level in Vietnam, it is necessary to set up separate human rights programs and integrate human rights into other relevant educational programs of all higher education institutions. Besides, it is necessary to improve professional capacity and  teaching methods for lecturers as well as to upgrade literature resources for teaching and research on human rights.